Temporal and spatial dynamics of the soil usage in the micro-region of Campanha Central do Rio Grande do Sul between the years of 1992 and 2010 - Brites, Daiana Iris Soto; Silva, Emanuel Araújo; Goergen, Laura Camila de Godoy; Nunes, Matheus Mesquita da Costa; Pereira, Rudiney Soares (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708706 This article aims to present the temporal evolution occurred on soil use in 1992 and 2010 in the microregion Central Campaign of Rio Grande do Sul, giving prominence to forests´ transition. The images from the Landsat TM sensor platform 5 and the Spring application, was classified images, determining the following land use classes: bare soil, water, agricultural use, sand, native forest and plantation forests. For the generation of thematic maps was used to LEGAL Analysis (GIS Spatial Algebraic Language), tool that enables spatial analysis using map algebra. From the generation of thematic maps were calculated areas where there was the expansion of native forests (7.55% of total area) - areas where natural regeneration has occurred, becoming forest in 2010. The area that has remained the use of native forest over 18 years is 2.83% of the total area. Deforestation, forest areas belonging to native and has reverted to another use, is 1.23%. Reforestation, represented by the areas that now belong to the class planted forest was quantified at 0.57% of the total area of microregion. The remaining land use change (86.98% of total area) were among the other classes of land use. The work allowed us to observe the changes in land use over a period of 18 years, it was observed an increase in forest area, both native and planted. This increase is probably related to the investment in the forest sector in the region since 2005, accompanied by the abandonment of land unwieldy and increase the rigor of the law.